"Rising prices of petrol and diesel in India since 2014: An Analytical Study" - Dr. Dinesh Gabhane, Madhuri Gabhane (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
With the rapid growth in economy, India has been third largest importer of crude oil in the world surpassing china in mid-2020 and fulfils over 84% of its oil requirement through import. This paper attempts to study the causes for rising prices of petrol and diesel and its effect on Indian economy. Rising prices of crude oil put severe pressure on the economy, the cause being; demand and supply equation; OPEC policy; hefty taxation levied by government on petroleum products and exchange rate of rupee against dollar. It has been found that the rising prices of fuel have several implications in term of pushing up manufacturing cost; high inflation rate; low GDP growth, increase in current account deficit (CAD) & fiscal imbalance, effect on industries and rise in transportation cost and essential commodities. It has been concluded that international crude oil prices has nothing to do with retail prices of petrol and diesel but the real culprit is taxation policy of both central and state government.